DATA ON THE COMPOSITION OF BEETLES (COLEOPTERA) IN XUAN NHA NATURE RESERVE, SON LA PROVINCE - Bao Thanh, Le (Journal of Forestry Science and Technology, 2017)
Beetle sampling was conducted on transects in Xuan Nha Nature Reserve, Son La Province using hand searching on the ground and trees, pitfall traps, light traps and fly interception traps. A total of 129 species belonging to 11 families were recorded. In which, the most abundant family was Scarabaeidae with 39 species accounting for 30.2% the total number of the recorded species, Chrsomelidae accounted for 17.8%, Coccinellidae accounted for 14.7%, Cerambycidae accounted for 13.2%, Curculionidae accounted for 7.8%, Buprestidae accounted for 6,2%, and Tenebrionidae, Elateridae and Anobiidae acounted for 2.3%. The two sub families Meloidae and Anthribidae indicated the lower number of species accounting for 1.6%. Scarabaeidae contributed the highest number of genera accounting for 31.4% the total number of the genera, Cerambycidae accounted for 18.6%, Coccinellidae accounted for 12.8%, Chrsomelidae accounted for 11.6%, Curculionidae accounted for 9.3%, Elateridae and Tenebrionidae accounted for 3.5%, the remaining families accounted for only 2.3%. More than 70% the total number of the species were rare species. The common species accounted for 21%, and the species were collected randomly accounting for 6%. The meadows had the high number of species accounting for 36.8% the total number of the species, the residential habitats accounted for 35,3%, the primary forests accounted for 22.5%, the secondary forests accounted for 22.1%, the agricultural habitats accounted for 19.9%, the bamboo forests accounted for 8.5%. The phytophaga species (leaves, bark, stems, root shoots) accounted for 62%, the necrophaga, detritophaga and corprophaga species accounted for 21.7%, the zoo phaga species accounted for 14.7%. Two species have not been identified yet accounting for 1.6%.